2006
DOI: 10.1007/s00134-006-0134-5
|View full text |Cite
|
Sign up to set email alerts
|

Expanding ICU facilities in an epidemic: recommendations based on experience from the SARS epidemic in Hong Kong and Singapore

Abstract: Epidemics have the potential to severely strain intensive care resources and may require an increase in intensive care capability. Few intensivists have direct experience of rapidly expanding intensive care services in response to an epidemic. This contribution presents the recommendations of an expert group from Hong Kong and Singapore who had direct experience of expanding intensive care services in response to the epidemic of severe acute respiratory syndrome. These recommendations cover training, infection… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
128
0
1

Year Published

2006
2006
2021
2021

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 76 publications
(129 citation statements)
references
References 38 publications
0
128
0
1
Order By: Relevance
“…13 This is an opinion supported by others who also concluded that adequately trained staff was likely to be the limiting factor in providing ventilatory support in a pandemic. 6 Let us briefly examine why this is so.…”
Section: Expanding Icu Capacitymentioning
confidence: 88%
See 4 more Smart Citations
“…13 This is an opinion supported by others who also concluded that adequately trained staff was likely to be the limiting factor in providing ventilatory support in a pandemic. 6 Let us briefly examine why this is so.…”
Section: Expanding Icu Capacitymentioning
confidence: 88%
“…13 In practical terms, an 'ICU bed' is a unit made up of a physical space containing a bed with attendant power, gas supplies and life-support equipment, serviced by specialist doctors, nurses and allied health staff. This unit can only function well with much additional support, including radiology, physiotherapy, laboratory and laundry SASA Refresher Text services.…”
Section: Expanding Icu Capacitymentioning
confidence: 99%
See 3 more Smart Citations